Facile synthesis of CuO mesocrystal/MWCNT composites as anode materials for high areal capacity lithium ion batteries. Issue 10 (1st August 2016) - Xu, Junmin; Liu, Yongfei; He, Lei; Zhang, Changjin; Zhang, Yuheng
Abstract: CuO mesocrystal entangled with multi-wall carbon nanotube (MWCNT) composites are synthesized through a facile scalable precipitation and a followed oriented aggregation process. When evaluated as anode materials for lithium ion batteries, the CuO-MWCNT composites exhibit high areal capacity and good cycling stability (1.11 mA h cm −2 after 400 cycles at the current density of 0.39 mA cm −2 ). The excellent electrochemical performance can be ascribed to the synergy effect of the unique structure of defect-rich CuO mesocrystals and the flexible conductive MWCNTs. The assembled architecture of CuO mesocrystals can favor the Li-ion transport and accommodate the volume change effectively, as well as possess the structural and chemical stability of bulk materials, while the entangled MWCNTs can maintain the structural and electrical integrity of the electrode during the cycles.